Local impacts of the global shrimp industry: Mangrove clearings, shrimp farms and environmental justice in Sabah, Malaysia - David Michael Buchwinkler (Südwind-Verlag, 2022)
An increasing variety of exotic foods including shrimp and other seafood has become readily available for consumers in Austria as well as in other advanced countries. The development from seafood commanding the status of a delicacy served only at special occasions to becoming almost a household staple is in fact a rather recent phenomenon. It has all to do with reconfigurations having taken place in global economy during the last three decades. Propelled by the debt crisis of the 1980s, a large number of low-income countries in Africa and Asia was advised by the World Bank and other international agencies to conduct economic reforms to diversify their exports. In many cases, this included the promotion of non-traditional agricultural and food commodities. Their production for export promised countries to earn much-needed foreign exchange as well as to boost employment. While the benign economic consequences of this policy can be seen in our supermarket shelves, it is hardly noted that the large-scale expansion of non-traditional agricultural production came at the price of significant social and environmental impacts upon local communities in the Global South. David Buchwinkler takes up this important issue in his Master's thesis. He is precisely writing on the environmental and social consequences of intensive shrimp aquaculture in the Malaysian state of Sabah. He focuses on a case study of the large-scale aquaculture project in the Pitas district, where he analyzeses the impacts on the local population and how the local population perceives and deals with the economic, social and environmental consequences of this project. Hence, the thesis adds a relevant country case to the literature on the social and environmental consequences of aquaculture. Key findings of the thesis state that shrimp producers are in a precarious economic and social position given large price fluctuations and declining margins. Besides these economic and social issues, native customary practices and land rights are central issues in the case study and illustrate how the negligence of the identities of local indigenous communities and of the environmental heritage have led to distributive, participatory and procedural injustices. These injustices are rooted both in local power structures, but also in practices and dynamics in the global shrimp aquaculture industry and in power asymmetries in the related global production network. The results of this study are thus not only a critical reminder for consumers in Austria and other advanced industrial countries to critically reflect on their consumption habits, or, for that matter, for supermarket chains to interrogate their sourcing practices. They also provide important lessons for European development cooperation. Economic programms to foster exports of non-traditional agricultural and food products from the Global South to Europe need to address the social and environmental dimension of production and mitigate negative impacts on local populations and the environment.
Keywords: 330